Changes in Cooking Qualities, Nutritional Composition and Shelf Life of Sweet Potato Stored Under Different Methods - Seema Thampy S (Department of Home Science, College of Agriculture, 1994)
The investigation on “changes in cooking qualities, nutritional composition and shelf life of sweet potato stored under different methods” was carried out to find out the keeping quality of sweet potato tuber with reference to extent of damage, changes in cooking organoloeptic and nutritional qualities of the tuber as influenced by different low cost storage treatments at various durations of storage. The results obtained are depicted below: